Childhood cancer survivors face markedly worse overall survival after diagnosis with breast cancer, melanoma, or colorectal cancer. Issue 1 (31st March 2021) - Lynch, Kevin T.; Kane, William J.; Fleming, Mark A.; Desai, Raj P.; Showalter, Shayna L.; Slingluff, Craig L.; Levin, Daniel E.; Hedrick, Traci L.
Abstract: Background: Childhood cancer survivors (CCS) are at elevated risk of secondary malignancies (SM). Enhanced screening for SM is recommended, but compliance is poor. We hypothesized that CCS with adult‐onset SM (colorectal cancer [CRC], melanoma, or breast cancer [BC]) would present with more advanced disease and have decreased overall survival (OS). Methods: The Surveillance, Epidemiology, and End Results Program was queried for patients diagnosed with cancer at age less than or equal to 18 also diagnosed with adult‐onset CRC, melanoma, or BC. A cohort without a history of prior malignancy was likewise identified. Tumor features and clinical outcomes were compared. Results: CCS with a SM ( n  = 224) were compared with patients without a childhood cancer history ( n  = 1, 392, 670). CCS were diagnosed younger (BC = 37.6 vs. 61.3, p  < 0.01, CRC = 35.0 vs. 67.1, p  < 0.01, melanoma = 29.6 vs. 61.3 years old, p  < 0.01). CCS with BC were more likely to have Stage III or IV disease (25.2% vs. 16.5%, p  = 0.01). Hormone‐receptor expression also differed; CCS were less likely to develop Luminal A‐type tumors (48.6% vs. 66.9%, p  = 0.01). After age‐adjustment, CCS had worse OS (Hazard ratio: CRC = 2.449, p  < 0.01, melanoma = 6.503, p  < 0.01, BC = 3.383, p  < 0.01). Conclusion: CCS were younger when diagnosed with a SM. After age‐adjustment, OS was diminished. Heightened surveillance may be necessary for CCS diagnosed with SM.